Observasi Kelas dan Lesson Study: Strategi Tingkatkan Profesionalisme Guru di SMPN 12 Bandung - Alvida Dzattadini; Riska Aggraeni; Muhammad Rauhan Eka Putra; Hopid Jidan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to explore the development of teacher professionalism through Classroom Observation and Lesson Study at SMP Negeri 12 Bandung. This approach involves collaboration between school principals, supervisors, and teachers in designing more effective teaching strategies. The process encompasses planning, implementation, reflection, and sustainability stages. The findings reveal that these methods enhance student participation, improve teaching quality, and foster a collaborative work culture among teachers. Lesson Study also benefits the development of teachers' innovative skills, supports project-based learning, and enhances documentation of best practices through the Merdeka MengajarPlatform. By integrating Classroom Observation and Lesson Study, SMP Negeri 12 Bandung has successfully established a sustainable model for teacher professional development.